Investigating the influence of diet diversity on infection outcomes in a bumble bee (Bombus impatiens) and microsporidian (Nosema bombi) host-pathogen system - Martinez, Abraham; Calhoun, Austin C.; Sadd, Ben M. (Frontiers in Insect Science, 2023)
Diet can have an array of both direct and indirect effects on an organism's health and fitness, which can influence the outcomes of host-pathogen interactions. Land use changes, which could impact diet quantity and quality, have imposed foraging stress on important natural and agricultural pollinators.Diet related stress could exacerbate existing negative impacts of pathogen infection. Accounting for most of its nutritional intake in terms of protein and many micronutrients, pollen can influence bee health through changes in immunity, infection, and various aspects of individual and colony fitness.We investigate how adult pollen consumption, pollen type, and pollen diversity influence bumble bee Bombus impatiens survival and infection outcomes for a microsporidian pathogen Nosema (Vairimorpha) bombi. Experimental pathogen exposures of larvae occurred in microcolonies and newly emerged adult workers were given one of three predominantly monofloral, polyfloral, or no pollen diets. Workers were assessed for size, pollen consumption, infection 8-days following adulteclosion, survival, and the presence of extracellular microsporidian spores at death. Pollen diet treatment, specifically absence of pollen, and infection independently reduced survival, but we saw no effects of pollen, pollen type, or pollen diet diversity on infection outcomes. The latter suggests infection outcomes were likely already set, prior to differential diets. Although infection outcomes were not altered by pollen diet in our study, it highlights both pathogen infection and pollen availability as important for bumble bee health, and these factors may interact at different stages of bumble bee development, at the colony level, or under different dietary regimes.